Livsoplysning og livsfilosofiske perspektiver - et uddannelsesmæssigt modsvar til tidens fokus på kompetenceudvikling - Thomsen, Lene Frølund (Grundtvig-Studier, 2002)
Fra livsoplysning og livsfilosofiske perspektiver- et uddannelsesmæssigt modsvar til tidens fokus på kompetenceudvikling [From ‘Life-enlightenment' and ‘life-philosophical’ perspectives – a pedagogic challenge to the contemporary focus on ‘competence-development ’] By Lene Frølund Viewed in the context of education, competence-development [kompetenceudvikling] is the sign of the times. Within current educational research, the concept of ‘competence’ seems to have been identified as post modernity’s answer to the question of how individuals can learn to bring and keep themselves abreast of development in a complex knowledge- and informationbased society which imposes requirements of control, skillful steering and readiness to adapt. The pedagogic theme which sets the agenda in this debate on post-modern educational ideals is emancipation-pedagogy [frigørelsespædagogik], which has its roots in the Frankfurt School and Critical Theory, and which reaches back to the ideals of Liberty and Reason in the Age of Enlightenment. Since the nineteen-seventies emancipation-pedagogy has almost exclusively set the pedagogic agenda in Denmark. With its background in a philosophy based upon scientific rationalism, it has made its essential objective the development of the pupil’s critical sense. Thus political education and, subsumed in this, the development of a democratic disposition [det demokratiske sindelag] have been prioritised, at the cost of a strengthening of the philosophical disposition [det filosofiske sindelag] - as in the discussion of the perennial questions of existence. It is this rational-scientific outlook upon education with which Regner Birkelund takes issue in his book, Livs-Oplysning [Life-enlightenment]. With a background in N. F. S. Grundtvig and K. E. Løgstrup his aim is to enquire how one may combine a vocation-orientated education with a humane educational orientation. The enquiry is centred about a concrete example within nursing - a pedagogic experiment which took place at Testrup Højskole between 1927 and 1975. This folk-highschool featured a course preliminary to the school of nursing where future nurses were to be taught general highschool subjects together with specialised nursing subjects. The ideal was a learning process which was motivated by enjoyment and free participation and thus where not only reason but also the heart was involved. From Testrup, Birkelund traces the thread back to Gr. and aims thus to demonstrate that it was Gr’s pedagogic ideas - and herein Gr’s concept of lifeenlightenment (livsoplysning)- which formed the basis of the experiment in Testrup. Birkelund hereby offers an excellent introduction to Gr’s educational ideas. With the historical-poetic as his point of departure, Birkelund leads us in the final section of the book from Gr. to Løgstrup, for he believes that Løgstrup’s ethical and aesthetic views - and herein his concept of existential enlightenment [tilværelsesoplysning] - are a further development of Gr’s philosophy of life-enlightenment. He thus sees Løgstrup as giving a contemporary currency to both Gr and the experiment at Testrup. The modernist critique which Birkelund formulates in Livs-Oplysning is carried further in the recently published anthology Eksistens og livsfilosofi [Existence and Life-philosophy], edited by Birkelund. Here a series of prominent Danish and Swedish scholars present some of the most epochmaking Danish, Swedish, German and French life-philosophers. The book works within the same framework of a pre-scientific perspective upon life as Livs-Oplysning: life is more than theories about life. It is this ‘more,’ this existential supervention, which life-philosophy endeavours to embrace, and it is the relevance of this life-perspective to the whole field of educational, social and health concerns that this book desires to assert. Among the lifephilosophers selected for presentation, Løgstrup and Gr. again appear along with, to name only a few, Jakob Knudsen, Hans Lipps, Søren Kierkegaard, Martin Buber and Hannah Arendt. Again, we are dealing with an important book which offers inspiring reading: but the book has its weak points. The foreword proposes that lifephilosophy rests upon a revolt against the overdominance of rationalism: but is this an adequate characterisation of life-philosophy? is it sufficiently discriminating to call both Løgstrup and Kierkegaard life-philosophers? Løgstrup himself (Opgør med Kierkegaard [Confrontation with Kierkegaard^) has argued that life-philosophy in many ways entails a confrontation with (Kierkegaard’s) existential philosophy. While both life-philosophy and existential philosophy represent a showdown with the rationalism cultivated by Enlightenment philosophers, they go about it in diverse ways.